BETWEEN THE NEW ROADS AND THE OLD ROADS: THE RELATIONSHIP BETWEEN CITIZENS AND THE POLITICAL SYSTEM (Andamios, Revista de Investigación Social, 2009)
In today’s democracies there is a reconfiguration in the public sphere relations that involves a change in the places of the old political actors while opening up a set of new ones. Therefore political parties have begun to share the citizenship’s representation and the demands channeling with a series of new actors that have grown up in the political field. However, there is no answer about the current role of the political parties as well as the new political actors in democracy. For these reasons, this paper analyses the relation between citizens and political system in the new democratic context by making a theoretical approach that is supported with two public opinion surveys.
Keywords: Political participation; democracy; political parties; new political actors; Mexico